2017
DOI: 10.1080/10749357.2017.1305644
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-frequency repetitive transcranial magnetic stimulation and neuromuscular electrical stimulation on upper extremity motor recovery in the early period after stroke: a preliminary study

Abstract: LF-rTMS with or without NMES seems to facilitate the motor recovery in the paretic hand of patients with acute/subacute ischemic stroke. TMS or the combination of TMS + NMES may be a promising additional therapy in upper limb motor training. Further studies with larger numbers of patients are needed to establish their effectiveness in upper limb motor rehabilitation of stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 28 publications
0
61
1
Order By: Relevance
“…The results show a pre-post treatment improvement on average of 4.3 FM points. Tosun et al (2017) showed in a larger group of stroke patients that low frequency repetitive TMS alone and with neuromuscular electrical stimulation of wrist extensors significantly enhance motor recovery in the paretic hand more than conventional therapy.…”
Section: Combinations Of Interventionsmentioning
confidence: 97%
See 3 more Smart Citations
“…The results show a pre-post treatment improvement on average of 4.3 FM points. Tosun et al (2017) showed in a larger group of stroke patients that low frequency repetitive TMS alone and with neuromuscular electrical stimulation of wrist extensors significantly enhance motor recovery in the paretic hand more than conventional therapy.…”
Section: Combinations Of Interventionsmentioning
confidence: 97%
“…Here, 11 studies reporting muscular electrical stimulation effectiveness for stroke upper limb rehabilitation were selected (Dorsch et al , 2014; Kim et al , 2014; Quandt and Hummel, 2014; Knutson et al , 2015 a , b ; Liu et al , 2015; Vafadar et al , 2015; Wilson et al , 2016; Carda et al , 2017; Eraifej et al , 2017; Schick et al , 2017), and seven where muscular electrical stimulation was used in combination with other treatments (Koyama et al , 2014; Lee et al , 2015; Sattler et al , 2015, Jang et al , 2016; Kim et al , 2016; Rong et al , 2017; Tosun et al , 2017) (Table 1). In almost all of these studies, the muscular electrical stimulation elicits a movement and only in few cases, it is used solely for sensory stimulation (Wilson et al , 2016).…”
Section: Muscular Electrical Stimulationmentioning
confidence: 99%
See 2 more Smart Citations
“…It appears that the combination of rTMS with other recovery approaches, such as drugs, pharyngeal electrical stimulation, NMES, conventional rehabilitation, and task-oriented mirror therapy, achieves better therapeutic effects. 2225…”
Section: Introductionmentioning
confidence: 99%